Regional to National Health Insurance Integration Process in Bogor City, Indonesia - Rosmawati Upe (JUMP Health (Journal of Ultimate Public Health), 2018)
Background: Before the new national health insurance (Jaminan Kesehatan Nasional or JKN) has mandated to integrate all social state insurance including the previous national health insurance (Jamkesmas) and to the regional health insurance (Jamkesda), it was running difference between regionals in Indonesia due to financial capacities of each of regionals respectively. Bogor City has been known as the pilot city that successful to implement the Jamkesda. This study aims specifically to evaluate participant issue in the integration process of Jamkesda to JKN in Bogor City. Methods: Qualitative approach held in three main subjects that consisted of citizen/JKN patient, state and private hospitals, and the Health and Social Office. Results: It shows the perceived of the obstacle in having medical care by the patient at hospitals due to none JKN participant. Prior Jamkesmas participants systematically integrate as JKN participant while it differs with prior Jamkesda participants particularly in having medical care at private hospitals. Jamkesda participant who has expired enrollment would be direct to enroll as the new JKN participants for having the treatment in hospitals. Private hospitals perceived to apply the policy 72 hours to the none JKN patient either to have a warrant or to cover treatment from Health Offices as either JKN participants. Conclusions: The Local Government of Bogor City committed to set waiver as good political will in serving their citizens including taking free medical care without any warrant in the state hospital and accelerate the activation of the new polis handed JKN participant in private hospitals.